Dimensi Ekuitas Merek (Brand Equity) Dan Keputusan Pembelian Produk Mie Cepat Saji Di Kota Depok - Yanti Budiasih (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
Fact that Indomie (instant noodle) is a brand that most stick in the minds of consumers, and it is the evidence that Indomie has high brand equity. However, the facts also show that other brands are able to occupy under the Indomie brand equity. This paper presents an analysis of the influence of forming the dimensions of brand equity ie brand awareness, brand associations, perceived quality and brand loyalty on purchasing decisions on Indomie products. The population in this study were all the people in the city of Depok who consume Indomie. The sampling technique used was accidental sampling. The data are analyzed by using SPSS 19. The tools of analysis use correlation analysis, regression analysis, coefficients of determination, t-test (test partial) and F test (ANOVA test). The results showed that the dimensions of brand equity factors simultaneouslyinfluence the purchase decision. The most dominant factor influencing the purchase decision is brand associations that is equal to 31.1%.